Modeling of the reporting activities of a crane manufacturing organization - Thalmeiner Gergő; Gáspár Sándor; Zéman Zoltán; Gergo Talmeiner; Sandor Gaspar; Zoltan Zeman (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. Industrial manufacturing activity has changed significantly in recent years. In addition to standardized - mass production processes, customer - oriented individual production activities have become increasingly strong. In custom manufacturing with a customer focus, the customer is not only a passive observer but also an active participant in the design and manufacturing processes. Due to their unique nature, evaluating the performance of organizations can present a number of challenges. As a result of the development of digitalisation and economic IT innovations, an extensive system of tools is available, and a number of methods can be used to analyze the measured data. Among the analysis methodologies, the Key Performance Indicator (KPI) management, which is the basis of controlling systems, should be highlighted. As a result of the changes, the evaluation and expression of organizational performance should no longer focus on analyzing current conditions, but on forecasting expected future performance. In order to achieve this, the use of efficient infrastructure and professional and statistical-mathematical methods is formulated as a basic requirement. The interpretation of the information content of predictive KPIs and thus management decision support should depend on different assessments and standardization norms. Nowadays, organizational performance evaluation can be regarded as a basic controlling task, during which the goal is the extensive exploration and evaluation of organizational performance. Management is limitedly rational when making decisions, which means that it can only make decisions based on available information. The purpose of the controlling is to provide the management with a reporting activity that is suitable for evaluating the processes and making future-oriented decisions by uncovering extensive information and extensive methodological analysis of the data. It is therefore particularly emphasized that management should no longer be reactive, but proactive, which can be achieved by evaluating predictive analyzes and making decisions based on the information derived from the predictive evaluations.

Az ipari feldolgozóipari tevékenység jelentősen megváltozott az elmúlt években. A szabványosított - tömeggyártási folyamatok mellett egyre inkább felerősödtek a vevőorientált egyedi termelési tevékenységek. Az ügyfélközpontú egyedi gyártás során a vevő nem csak passzív megfigyelője, hanem aktív résztvevője is a tervezési és gyártási folyamatoknak. Egyedi jellegükből adódóan a szervezetek teljesítményének értékelése számos kihívást jelenthet. A digitalizáció és a gazdasági informatikai innovációk fejlődésének köszönhetően kiterjedt eszközrendszer áll rendelkezésre és számos módszer alkalmazható a mért adatok elemzésére. Az elemzési módszertanok közül kiemelendő a kontrolling rendszerek alapját képező Key Performance Indicator (KPI) menedzsment. A változások miatt a szervezeti teljesítmény értékelése és kifejezése már nem a jelenlegi állapotok elemzésére, hanem a várható jövőbeni teljesítmény előrejelzésére irányul. Ennek elérése érdekében alapvető követelményként fogalmazódik meg a hatékony infrastruktúra, valamint a szakmai és statisztikai-matematikai módszerek alkalmazása. A prediktív KPI információtartalmának értelmezése és így a vezetői döntéstámogatás a különböző értékelésektől és szabványosítási normáktól függ. Napjainkban a szervezeti teljesítményértékelés alapvető kontrolling feladatnak tekinthető, melynek során a szervezeti teljesítmény széleskörű feltárása, értékelése a cél. A vezetés korlátozottan racionális a döntések meghozatalakor, ami azt jelenti, hogy csak a rendelkezésre álló információk alapján tud dönteni. A controlling célja, hogy a menedzsment számára olyan beszámolási tevékenységet biztosítson, amely alkalmas a folyamatok értékelésére és a jövőbe mutató döntések meghozatalára a kiterjedt információk feltárásával és az adatok kiterjedt módszertani elemzésével. Ezért kiemelten hangsúlyozzák, hogy a menedzsmentnek már nem reaktívnak, hanem proaktívnak kell lennie, ami a prediktív elemzések kiértékelésével és a prediktív értékelésekből származó információk alapján történő döntéshozatallal érhető el.

Резюме. Промислова виробнича діяльність за останні роки суттєво змінилася. На додаток до стандартизованих процесів масового виробництва все більше посилюється індивідуальна виробнича діяльність, орієнтована на клієнта. У виробництві на замовлення з орієнтацією на клієнта клієнт є не тільки пасивним спостерігачем, але й активним учасником процесів проектування та виробництва. Через їхню унікальну природу оцінка ефективності організацій може викликати ряд проблем. У результаті розвитку цифровізації та економічних ІТ-інновацій з’явилася розгалужена система інструментів, а для аналізу вимірюваних даних можна використовувати ряд методів. Серед методологій аналізу слід виділити управління ключовими показниками ефективності (KPI), що є основою систем контролінгу. У результаті змін оцінка та вираження ефективності організації більше не повинні зосереджуватися на аналізі поточних умов, а на прогнозуванні очікуваних майбутніх результатів. Для цього в якості базової вимоги сформульовано використання ефективної інфраструктури та професійних і статистико-математичних методів. Інтерпретація інформаційного змісту прогнозних KPI і, таким чином, підтримка управлінських рішень має залежати від різних оцінок і норм стандартизації. Це забезпечує більш точну та реалістичну оцінку діяльності організації. Сьогодні оцінку ефективності організації можна розглядати як основне контрольне завдання, метою якого є широке дослідження та оцінка діяльності організації. Управління обмежено раціонально приймає рішення, а це означає, що воно може приймати рішення лише на основі наявної інформації. Мета контролюючої діяльності полягає в тому, щоб забезпечити керівництво звітністю, яка підходить для оцінки процесів і прийняття орієнтованих на майбутнє рішень шляхом розкриття обширної інформації та широкого методологічного аналізу. Тому особливо підкреслюється, що управління більше не повинно бути реактивним, а проактивним, чого можна досягти шляхом прогнозного аналізу та прийняття рішень на основі інформації, отриманої з прогнозних оцінок.
Darugyártó szervezet jelentési tevékenységének modellezése
Моделювання звітної діяльності крановиробничої організації
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: performance evaluation; controlling; reporting; KPI management; modeling